Patriarchal status of the UGCC as a "shifting coin" between the Vatican and Moscow (as the pontificate of Pope Francis) - Pavlo Pavlenko (Українське Pелігієзнавство, 2016)
Cardinal Lubomir Husar stipulates the hiding of the project on the provision of the patriarchate of the UGCC by the fact that even its sounding, not to mention the implementation, provokes a "wave of protests" in the Vatican circles, because it says "the patriarchate of the UGCC will weaken the communion with the Successor of St. Apostle Peter, and hence - weaken the connection with the whole Catholic Church, "" will mean the creation of a nationalist colored Church that will sow hatred against all others, "will become a" major obstacle to the unification of Christians in Ukraine ", will lead to" neglect of the rights of the Moscow the patriarchate, which considers Ukraine to be its canonical territory, "to the preservation of" uniticism ", which in our time was condemned as an inappropriate way to achieve unity among all Christians"